PENGARUH KONSENTRASI HORMON GIBERELIN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN OKRA - Farida Farida; Nani Rohaeni (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2019)
The effect of gibberellins hormone concentration on the growth and yield of okra. The aims of research are (1) to determinate the effects of growth and yield of okra plant with gibberellins hormon treatment, (2) to determine the best concentration of gibberellns hormone on the growth and yield of okra plants. This research obtained for three mounth on January to Aprl 2018. The research was conducted in Diponegoro Street, Village Sangatta Sub-distrct East Kutai. This research uses is Completely Randomized Design (CRD) of non factorial experiments each of four treatments and six replcates, are : g0 = without fertilizer, g1 = 150 ppm, g2 = 200 ppm, g3 = 250 ppm. The obtained data was analyzed by F test 1% and 5% and be continued with LSD at 5% if the treatment had significant effect. The results of the best growth research plant height 7 MST (75,141 cm) and growth of the leaves number 7 MST, best flowering age at 32,167 day and the best yield production result is 971,333 gram solid treatment.